2018
DOI: 10.1002/jcb.27568
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐125b suppresses the carcinogenesis of osteosarcoma cells via the MAPK‐STAT3 pathway

Abstract: The microRNA (miRNA) miR‐125b is abnormally expressed in many different types of tumors, including osteosarcoma (OS). How aberrantly expressed miR‐125b participates in regulating the initiation and progression of OS is still poorly understood. In the current study, we found that in OS, miR‐125b can suppress the expression of MAP kinase kinase 7 (MKK7), which can dephosphorylate and inactivate signal transducer and activator of transcription 3 (STAT3). We also identified an elevated expression level of MKK7 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
(112 reference statements)
0
14
0
Order By: Relevance
“…In recent, accumulating evidence demonstrated that several miRNAs were dysregulated in types of tumors, and the oncogenic or anti-cancer roles of miRNA were obvious in various cancers [2426]. For example, miR-125b has been found to play a vital role in the development of malignant tumors [3]. MiR-590 regulated the chemoresistance of osteosarcoma by targeting wild-type p53-induced phosphatase 1 (WIP1) [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent, accumulating evidence demonstrated that several miRNAs were dysregulated in types of tumors, and the oncogenic or anti-cancer roles of miRNA were obvious in various cancers [2426]. For example, miR-125b has been found to play a vital role in the development of malignant tumors [3]. MiR-590 regulated the chemoresistance of osteosarcoma by targeting wild-type p53-induced phosphatase 1 (WIP1) [27].…”
Section: Discussionmentioning
confidence: 99%
“…Osteosarcoma (OS) is regarded as the most prevalent malignant bone cancer, which generally appears in the long bones of limbs as well as the growth plate nearby the metaphyseal [1, 2]. According to the reports, OS is usually observed in young adults and adolescents, and accounts for about 2.4% of all malignant tumors in children and exceeds about 20% of all primary bone cancers [3]. According to the reports, the morbidity of OS has reached approximately one to three cases annually per million all over the world [4].…”
Section: Introductionmentioning
confidence: 99%
“…MAPKs are also involved in numerous diseases. Xiao proved that miR-125b attenuates the carcinogenic progression of osteosarcoma cells by regulating the MAPK-STAT3 signaling pathway [25], and Han et al confirmed that micro-RNA-128 contributed to gastric carcinoma progression by activating GAREM-mediated MAPK signaling [26]. In the hypoxia/reoxygenation injury model, antiphospholipid antibody can affect the apoptosis of neonatal rat cardiomyocytes by regulating the p38 MAPK signaling pathway [27].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 98%
“…miR-143 and miR-125b directly targets MAPK7 and suppresses MAPK7 expression in OS cells. These miRNAs suppress cell growth and invasion and migration [67,68]. Cyclin-dependent kinase 4 (CDK4) and mouse double minute 2 homolog (MDM2) are genes located in 12q13–q14.…”
Section: The Functions Of Mirna and Exosomes In Sarcomamentioning
confidence: 99%